Sea buckthorn cultivars promising for mechanized harvesting by cutting fruit-bearing branches - Yu. A. Zubarev; A. V. Gunin; E. I. Panteleeva; A. V. Vorobyeva (Труды по прикладной ботанике, генетике и селекции)
Background. Sea buckthorn (Hippophae rhamnoides L.) is the main berry crop in the horticultural production of Altai Territory and occupies the largest growing area among berries in Russia. Meanwhile, further expansion of commercial plantations is limited by known bottlenecks in harvesting. In this context, new technological solutions in harvest mechanization are considered one of the primary tasks. A promising way is the cutting of fruit-bearing branches. At the same time, the development of cultivars suitable for such harvesting technique is very important.Materials and methods. Thirteen cultivars and selected forms of sea buckthorn developed at the Federal Altai Scientific Center of Agro-Biotechnologies were taken as research material. To evaluate the productivity of top branches, three of them with a length of 70–100 cm were cut from the plants of each accession. Fruit detachment force was assessed using a Dina-2 device. Dispersion analysis was applied for statistical interpretation.Results. Productivity of top branches as well as agronomic and biological characteristics of sea buckthorn fruits were studied. Accessions 87-93-1, 111-05-3 and 378-06-1 were identified for high productivity of their top branches and for predomination of the generative part over the vegetative one. The highest number of berries per bud (5.4–5.9 pieces) was observed in accessions 87-93-4, 32-01-1, 378-06-1 and 111-05-3. Cv. ‘Afina’ demonstrated for its high level of vegetative and generative productivity. Selected forms 111-05-3, 32-01-1 and 4-93-11 with low fruit detachment force (136.8–155.1 g) are promising for shaking without prior freezing.Conclusion. Selected forms 111-05-3, 378-06-1 and 32-01-1 were recognized as most promising for harvesting by branch cutting.